Evaluation of bone substitutes for treatment of peri-implant bone defects: Biomechanical, histological, and immunohistochemical analyses in the rabbit tibia - dos Santos, Pâmela Letícia; de Molon, Rafael Scaf [UNESP]; Queiroz, Thallita Pereira; Okamoto, Roberta [UNESP]; de Souza Faloni, Ana Paula; Gulinelli, Jéssica Lemos; Luvizuto, Eloá Rodrigues [UNESP]; Garcia, Idelmo Rangel [UNESP] (XMLink, 2016)
Purpose: We sought to evaluate the effectiveness of bone substitutes in circumferential periimplant defects created in the rabbit tibia. Methods: Thirty rabbits received 45 implants in their left and right tibia. A circumferential bone defect (6.1 mm in diameter/4 mm depth) was created in each rabbit tibia using a trephine bur. A dental implant (4.1 mm × 8.5 mm) was installed after the creation of the defect, providing a 2-mm gap. The bone defect gaps between the implant and the bone were randomly filled according to the following groups: blood clot (CO), particulate Bio-Oss® (BI), and Bio-Oss® Collagen (BC). Ten animals were euthanized after periods of 15, 30, and 60 days. Biomechanical analysis by means of the removal torque of the implants, as well as histologic and immunohistochemical analyses for protein expression of osteocalcin (OC), Runx2, OPG, RANKL, and TRAP were evaluated. Results: For biomechanics, BC showed a better biological response (61.00± 15.28 Ncm) than CO (31.60± 14.38 Ncm) at 30 days. Immunohistochemical analysis showed significantly different OC expression in CO and BC at 15 days, and also between the CO and BI groups, and between the CO and BC groups at 60 days. After 15 days, Runx2 expression was significantly different in the BI group compared to the CO and BC groups. RANKL expression was significantly different in the BI and CO groups and between the BI and BC groups at 15 days, and also between the BI and CO groups at 60 days. OPG expression was significantly higher at 60 days postoperatively in the BI group than the CO group. Conclusions: Collectively, our data indicate that, compared to CO and BI, BC offered better bone healing, which was characterized by greater RUNX2, OC, and OPG immunolabeling, and required greater reversal torque for implant removal. Indeed, along with BI, BC presents promising biomechanical and biological properties supporting its possible use in osteoconductive grafts for filling peri-implant gaps.
Keywords: Bone substitutes; Bone transplantation; Dental implantation; Osseointegration; Rabbits